2009
DOI: 10.1186/1756-8935-2-15
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of RNA polymerase II and the small RNA machinery affects heterochromatic silencing in Drosophila

Abstract: BackgroundHeterochromatin is the tightly packaged dynamic region of the eukaryotic chromosome that plays a vital role in cellular processes such as mitosis and meiotic recombination. Recent experiments in Schizosaccharomyces pombe have revealed the structure of centromeric heterochromatin is affected in RNAi pathway mutants. It has also been shown in fission yeast that the heterochromatin barrier is traversed by RNA Pol II and that the passage of RNA Pol II through heterochromatin is important for heterochroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 39 publications
0
31
0
Order By: Relevance
“…Possibly, particular Piwiregulated transposons avoid the degradation by Aub/Ago-3 cytoplasmic piRNA machinery as a result of their masking by cytoplasmic proteins. Several reports have implicated Piwi in chromatin status maintenance (8,(39)(40)(41)(42)(43). We revealed that the loss of the nuclear Piwi in the piwi Nt ovaries enriches the chromatin context of telomeric transposons with H3K4me2 euchromatic marks and decreases the occupancy of heterochromatic marks such as H3K9me2/3 histones and HP1 protein (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Possibly, particular Piwiregulated transposons avoid the degradation by Aub/Ago-3 cytoplasmic piRNA machinery as a result of their masking by cytoplasmic proteins. Several reports have implicated Piwi in chromatin status maintenance (8,(39)(40)(41)(42)(43). We revealed that the loss of the nuclear Piwi in the piwi Nt ovaries enriches the chromatin context of telomeric transposons with H3K4me2 euchromatic marks and decreases the occupancy of heterochromatic marks such as H3K9me2/3 histones and HP1 protein (Fig.…”
Section: Discussionmentioning
confidence: 63%
“…Some rasiRNAs are implicated in silencing heterochromatin in plants, fungi, and Drosophila, where ribonucleoprotein (RNP) complexes associated with rasiRNAs recruit silencing factors to the chromatin (Pal-Bhadra et al 2004;Verdel et al 2004;Buhler and Moazed 2007;Kavi and Birchler 2009;Wang and Elgin 2011). The most famous rasiRNA pathway in the germline is the Piwi pathway including P-elementinduced wimpy testis (Piwi), Aubergine (Aub), and Argonaute 3 (Ago3).…”
Section: Segregation Distortion and Small Rnasmentioning
confidence: 99%
“…If SD/SD + heterozygotes suffer disrupted nuclear transport during spermatogenesis, then Rsp rasiRNAs, after associating with RNP complexes in the cytoplasm, may not be efficiently imported back into the nucleus for targeting to the Rsp satellite ( Figure 7C). Presumably the rasiRNAs direct chromatin remodeling complexes after meiosis in the testis, similar to RNAi-dependent heterochromatin formation in somatic tissues (Pal-Bhadra et al 2004;Kavi and Birchler 2009). Because Rsp s alleles have many (and Rsp i alleles have few) repeats, Rsp s -bearing spermatids might be disproportionately affected by the dearth of Rsp rasiRNAs in the nucleus and as a result fail to condense their pericentric heterochromatin (Ferree and Barbash 2007;Tao et al 2007).…”
Section: Segregation Distortion and Small Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, to test whether the heterozygous JIL-1 z2 allele could counterbalance the suppression of the Su(var)3-9 06 or Su(var)2-5 05 loss-of-function alleles of the PEV of 118E-10, we compared the eye pigment levels of the various genotypes (Figures 1 and 2 and Table 1). Pigment assays were performed essentially as in Kavi and Birchler (2009) using three sets of 10 pooled fly heads from each genotype. Although both male and female flies were scored, due to sex differences only results from male flies are shown.…”
mentioning
confidence: 99%